Penerapan Distribusi Zero Modified Poisson pada Data Jumlah Gol Tim Tandang Liga Sepak Bola Indonesia - Maulana Ilham Pratama; Aceng Komarudin Mutaqin (UNISBA Press, 2023)
Abstract. The Indonesian League, which is currently known as the Indonesia Super League (ISL) or Liga 1, is the highest caste football competition between clubs in Indonesia. The Indonesian League was held for the first time in 1994 (the competition system was divided into 2 regions) which was a merger between the previous major competitions. Many researchers from various countries have carried out the application of distributions to football sports data cases to find out what odds distributions are suitable for modeling the number of goals scored in home and away games in a league. Distributions that can be used to model data on the number of goals scored in soccer matches include the Poisson distribution, negative binomial, Poisson-Lindley, and Zero-Inflated Poisson. In a football match, it is generally difficult for the away team to score goals. One of the discrete distributions for the case of the Poisson distribution when there are many zeros is the Zero-Modified Poisson distribution. In this thesis, the ZMP distribution will be applied to the data on the number of goals scored by the away team in the Indonesian Football League. The maximum likelihood estimator method is used to estimate the parameters of the discrete distribution. While the distribution fit test to be used is the chi-square test. As the application material, data on the results of the 2017-2018 Indonesian League football matches will be used. Based on the results of an analysis of the application of the Zero-Modified Poisson distribution to data on the number of goals scored by the Indonesian League 1 away team in 2017-2018, it can be concluded that the Zero-Modified Poisson distribution is suitable for modeling the frequency data of the number of goals scored by the Indonesian League 1 away team in 2017-2018. Abstrak. Liga Indonesia yang pada saat ini dikenal dengan Indonesia Super League (ISL) atau liga 1 adalah kompetisi sepak bola kasta tertinggi antar klub di Indonesia. Liga Indonesia diselenggarakan pertama kali pada tahun 1994 (sistem kompetisi dibagi 2 wilayah) yang merupakan penggabungan antara kompetisi besar sebelumnya. Penerapan distribusi pada kasus data olahraga sepak bola sudah banyak dilakukan oleh peneliti-peneliti dari berbagai negara untuk mengetahui distribusi peluang apa yang cocok untuk memodelkan jumlah gol dalam pertandingan kandang dan tandang dalam suatu Liga. Distribusi yang bisa digunakan untuk memodelkan data jumlah gol hasil pertandingan sepak bola diantaranya adalah distribusi Poisson, binomial negatif, Poisson-Lindley, dan Zero-Inflated Poisson. Dalam suatu pertandingan sepakbola, umumnya tim tandang selalu kesulitan untuk mencetak gol. Salah satu distribusi diskrit untuk kasus distribusi Poisson ketika nilai nol-nya banyak adalah distribusi Zero-Modified Poisson. Dalam skripsi ini akan diterapkan distribusi ZMP pada data jumlah gol tim tandang Liga sepak bola Indonesia. Metode penaksir kemungkinan maksimum digunakan untuk menaksir parameter pada distribusi diskrit tersebut. Sedangkan uji kecocokan distribusi yang akan digunakan adalah uji chi-kuadrat. Sebagai bahan aplikasi akan digunakan data hasil pertandingan sepak bola Liga Indonesia tahun 2017-2018. Berdasarkan hasil analisi penerapan distribusi Zero-Modified Poisson pada data jumlah gol tim tandang Liga 1 Indonesia tahun 2017-2018 dapat disimpulkan bahwa distribusi Zero-Modified Poisson cocok untuk memodelkan data frekuensi jumlah gol tim tandang Liga 1 Indonesia tahun 2017-2018.